Computer-Based Archive Management at the West Java Regional Customs Office - Fallya Nurfaiza Rahman; Muhammad Taufiq (Trescode Green Organization, 2024)
Effective archive management is a cornerstone of good governance, serving as the collective memory and legal accountability framework for state institutions. This community service project aims to modernize the archival system at the West Java Customs Regional Office by transitioning from conventional manual methods to a robust computer-based management system. The initiative is strategically aligned with the Indonesian National Work Competency Standard (SKKNI) No. 39 of 2019, specifically unit O.84ARS00.066.1 regarding computer-based archive storage. The implementation methodology followed a systematic three-stage approach: a preparation stage involving in-depth needs analysis and resource mobilization; an implementation stage encompassing intensive technical training and the deployment of the Nadine and Satu Kemenkeu digital ecosystems; and an evaluation stage to measure system performance and user satisfaction. The theoretical framework of this project incorporates recent literature on digital transformation, highlighting that service quality and system reliability are primary determinants of public trust in e-government ecosystems. Furthermore, the study acknowledges that technical innovation must be balanced with high Public Service Motivation (PSM), as proactive work behavior among archivists is the ultimate catalyst for successful administrative reform. Results indicate a significant transformation in operational efficiency; document retrieval times were reduced from hours to seconds, and the risks associated with physical data degradation were effectively mitigated through centralized data centers and encrypted security protocols. Moreover, the systematic sorting and lifecycle management of trade facility documents, such as KITE and sub-contract approvals, ensured legal compliance and optimized storage resources. This project concludes that the synergy between advanced digital infrastructure and competent, motivated human resources is essential for achieving sustainable, transparent, and accountable public service delivery in the modern era.